2012
DOI: 10.1167/iovs.11-9055
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Choroidal and Optic Nerve Head Blood Flow Regulation during Changes in Ocular Perfusion Pressure

Abstract: PURPOSE. We compared the response of choroidal and optic nerve head blood flow (ChBF, ONHBF) in response to an increase in ocular perfusion pressure (OPP) during isometric exercise and during a decrease in OPP during an artificial increase in intraocular pressure (IOP). METHODS.We included 96 healthy subjects in our study. In 48 subjects OPP was increased by 6 minutes of squatting, and either ONHBF (n ¼ 24) or ChBF (n ¼ 24) was measured continuously. In 48 other healthy subjects either ONHBF (n ¼ 24) or ChBF (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
70
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 61 publications
9
70
1
1
Order By: Relevance
“…This is in accordance with data from a previous study performed in our laboratory, where autoregulation in the ONH started to fail at OPP values of 66% over baseline. 11 In contrast, a similar study performed by Movaffaghy et al found no cutoff point for the upper limit up ONHBF autoregulation, but their study participants only reached OPP values of 30 6 8% over baseline. 22 As in the choroid, NO is an important regulator of basal blood flow in the ONH, since administration of L-NMMA significantly decreased ONHBF.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…This is in accordance with data from a previous study performed in our laboratory, where autoregulation in the ONH started to fail at OPP values of 66% over baseline. 11 In contrast, a similar study performed by Movaffaghy et al found no cutoff point for the upper limit up ONHBF autoregulation, but their study participants only reached OPP values of 30 6 8% over baseline. 22 As in the choroid, NO is an important regulator of basal blood flow in the ONH, since administration of L-NMMA significantly decreased ONHBF.…”
Section: Discussionmentioning
confidence: 57%
“…11,22 As shown in Figure 6, ONHBF started to increase significantly when OPP was raised to values between 55% and 70% over baseline, when no drug or placebo was administered. This is in accordance with data from a previous study performed in our laboratory, where autoregulation in the ONH started to fail at OPP values of 66% over baseline.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…63 It would be interesting to also analyze data when OPP is decreased. We have done some experiments during a suction cup-induced increase in IOP, 33,34,53,81 but the number of subjects included in these previous studies is not sufficient to allow for the type of analysis applied in this report. Given that LDF was used in our experiments, measurements of blood flow are restricted to the subfoveal choroid.…”
Section: Discussionmentioning
confidence: 99%